Nutrition as Metabolic Treatment for Anxiety - Norwitz, Nicholas G.; Naidoo, Uma (Frontiers in Psychiatry, 2021)
Despite the overwhelming prevalence of anxiety disorders in modern society, medications and psychotherapy often fail to achieve complete symptom resolution. A complementary approach to medicating symptoms is to address the underlying metabolic pathologies associated with mental illnesses and anxiety. This can be achieved through evidence-based nutritional interventions. In this review, we highlight the roles of the microbiome and inflammation as influencers of anxiety. We further discuss the mechanistic rationale and evidence base for six specific nutritional interventions: avoiding artificial sweeteners and gluten, including omega-3 fatty acids and turmeric in the diet, supplementation with vitamin D, and ketogenic diets. In addition to biological justifications and data from preclinical and clinical trials, we attempt to integrate insights from the nutrition science-literature in order to highlight some best practices that practitioners may consider when treating individual patients.